1991
DOI: 10.1002/yea.320070104
|View full text |Cite
|
Sign up to set email alerts
|

Scarcity of ars sequences isolated in a morphogenesis mutant of the yeast Yarrowia lipolytica

Abstract: Previous attempts is isolate autonomously replicating sequences (ars) from the dimorphic yeast Yarrowia lipolytica have been unsuccessful. We isolated a Fil- mutant unable to produce hyphae and growing only in a yeast form to facilitate ars isolation. This mutant was transformed with a Y. lipolytica DNA bank and several unstable clones were obtained. Extrachromosomal plasmids were evidenced in yeast, recovered in Escherichia coli and characterized by restriction mapping. They were able to retransform Fil- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Cells from smooth colonies were observed only in the budding form of growth. The frequency of mutants was 8.7 ϫ 10 Ϫ4 , similar to those described for Y. lipolytica by other authors (18,48).…”
Section: Isolation and Characterization Of Morphological Mutantssupporting
confidence: 87%
See 1 more Smart Citation
“…Cells from smooth colonies were observed only in the budding form of growth. The frequency of mutants was 8.7 ϫ 10 Ϫ4 , similar to those described for Y. lipolytica by other authors (18,48).…”
Section: Isolation and Characterization Of Morphological Mutantssupporting
confidence: 87%
“…lipolytica is a dimorphic heterothallic yeast (3) that is unusual in both the structure of its genes coding for rRNA (17) and in its relationship to other yeasts (2). Y. lipolytica is amenable to genetic analysis (48), and DNA-mediated integration (12,20) and autonomous transformation systems (18) have been developed. Mutations in the SEC14 gene (42) and deletion of XPR6 (16) have strong effects on the yeast-to-hypha transition.…”
mentioning
confidence: 99%
“…From a Y. lipolytica gene library, we had previously isolated the ARS18 and ARS68 sequences that are able to promote extrachromosomal replication in this yeast (27). We had shown that both ARS elements also have the ability to confer centromere-like segregation properties on yeast plasmids, and we had localized these characteristics to a 410-bp region in the case of ARS18 (26).…”
Section: Discussionmentioning
confidence: 99%
“…We previously cloned on plasmids two sequences (ARS18 and ARS68) able to promote extrachromosomal replication (27). These two ARS plasmids displayed a behavior different from that of traditional ARS elements in S. cerevisiae: low copy number, higher mitotic stability, and scarcity in a genomic DNA library.…”
Section: Although the Nature Of Higher Eukaryotic Replication Originsmentioning
confidence: 99%
See 1 more Smart Citation